Preparation and enhanced photocatalytic performance of AgCl/Bi2MoO6 heterojunction - Jonjana S. (2017)
© 2016 Elsevier B.V. AgCl/Bi 2 MoO 6 heterojunction photocatalysts were prepared by direct deposition of AgCl nanoparticles on Bi 2 MoO 6 nanoplates. The as-prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). There was the detection of cubic AgCl nanoparticles supported on orthorhombic Bi 2 MoO 6 nanoplates. Their photocatalytic performance was evaluated through degradation of rhodamine B (RhB) solution. The 10.0 wt% AgCl/Bi 2 MoO 6 heterojunction showed the highest performance in removing of RhB under visible light and was very stable in performing photocatalysis.